Attenuation of Acute Rat Renal Allograft Rejection by Apolipoprotein E-Mimetic Peptide. Issue 5 (May 2015) - Zakrzewicz, Anna; Kutlimuratov, Khusin; Atanasova, Srebrena; Zakrzewicz, Dariusz; Reichert, Martin; Schmitz, Jessica; Wilhelm, Jochen; Lochnit, Günter; Padberg, Winfried; Grau, Veronika
<x xml:space="preserve">Abstract</x> Background In addition to its well-described role in lipid metabolism, apolipoprotein E (ApoE) exerts immunomodulatory functions. A protective role of ApoE and ApoE-mimetic peptide (ApoE(133–149)) application was documented in several inflammatory disorders. In this study, we test the hypothesis that ApoE(133–149) promotes renal allograft survival. Methods Dark Agouti, Brown Norway, and Fischer 344 kidneys were transplanted to Lewis rats to investigate fatal and reversible acute rejection. Apolipoprotein E expression was assessed in intravascular leukocytes of renal grafts, in graft tissue and in recipient blood plasma. Recipients of Brown Norway kidneys were treated with ApoE(133–149), and graft survival was monitored until day 100. Graft infiltration, cytokine, and chemokine production were analyzed. Results Intravascular graft leukocytes and renal tissue obtained from animals undergoing reversible acute rejection expressed increased levels of ApoE mRNA, whereas during fatal rejection, ApoE expression was reduced or remained unchanged. Animals treated with ApoE(133–149) showed prolonged allograft survival, which was associated with a reduced infiltration of CD8 and α/β T-cell receptor–expressing cells, diminished Granzyme B mRNA expression, and decreased caspase-3 activation. Conclusions Endogenous ApoE overexpression and exogenous application of ApoE(133–149) seem to protect renal allografts from fatal acute rejection. This effect was associated with a reduced influx of cytotoxic T cells.